2009
DOI: 10.1007/s00167-009-0765-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of microfracture in professional basketball players

Abstract: Surgical treatment for chondral defects of the knee in competitive running and jumping athletes remains controversial. This study evaluated the performance outcomes of professional basketball players in the National Basketball Association (NBA) who underwent microfracture. Data from 24 professional basketball players from 1997 to 2006 was obtained and analyzed. NBA player efficiency ratings (PER) were calculated for two seasons before and after injury. A control group of 24 players was used for comparison. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 12 publications
4
128
0
3
Order By: Relevance
“…Namdari et al 12 evaluated performance in WNBA athletes who tore their ACL and found 78% returned to play in the WNBA, with only slight decreases in field goal percentage and steals per game compared with their preinjury levels. Namdari et al 11 and Cerynik et al 4 evaluated the outcomes of NBA players after microfracture and found a 67% and 79% return to the NBA, respectively. Both studies showed a decrease in minutes per game postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…Namdari et al 12 evaluated performance in WNBA athletes who tore their ACL and found 78% returned to play in the WNBA, with only slight decreases in field goal percentage and steals per game compared with their preinjury levels. Namdari et al 11 and Cerynik et al 4 evaluated the outcomes of NBA players after microfracture and found a 67% and 79% return to the NBA, respectively. Both studies showed a decrease in minutes per game postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this method of data acquisition has been used in multiple previous studies. 2,7,11,12,15,22,27,28 Additional limitations were the absence of patient-reported outcomes, small number of subjects, single sport, incomplete follow-up and career length for players still in the NFL, and inability to compare offensive lineman or special teams players with performance scoring. Additionally, inherent to this type of study, there are multiple unknown confounding variables, such as: underlying hip pathology (FAI or labral pathology) that may or may not have been corrected, unknown presurgical course including unknown conservative treatments, no direct physical contact to corroborate diagnosis or range of motion, and no access to operative reports to determine which operative technique was used.…”
Section: Discussionmentioning
confidence: 99%
“…The pioneer of microfracture (Steadman) has successfully utilized microfracture in degenerative arthritis (Miller, Steadman et al 2004). Although microfracture has been used in high-performance athletes (NFL) with excellent outcomes and return-toplay (Steadman, Miller et al 2003), other studies have shown less success in highperformance professional athletes, with low rates of return-to-sport and decreased performance if able to return (Cerynik, Lewullis et al 2009;Namdari, Baldwin et al 2009). Outcomes of microfracture are mixed.…”
Section: Discussionmentioning
confidence: 99%